# MATH demonstrate idea of leaving gaps in an expression
# and then filling them in afterwards
# the examples given leave a lot to be desired!
[
hear] ((? x / = 10 / + 7 / x) 3);

[hear] ((? x / = 5 / + 2 / x) 3);

[hear] ((? x / = 20 / + 7 / x) 13);

[hear] ((? x / = 24 / + 13 / x) 11);

[hear] ((? x / = 19 / + 10 / x) 9);

[hear] ((? x / = 8 / + 0 / x) 8);

[hear] ((? x / = 17 / + 8 / x) 9);

[hear] ((? x / = 13 / + 7 / x) 6);

[hear] (((? x / ? y / = 1 / * (x) (y)) 1) 1);

[hear] (((? x / ? y / = 11 / * (x) (y)) 11) 1);

[hear] (((? x / ? y / = 22 / * (x) (y)) 2) 11);

[hear] (((? x / ? y / = 120 / * (x) (y)) 15) 8);

[hear] (((? x / ? y / = 50 / * (x) (y)) 5) 10);

[hear] (((? x / ? y / = 32 / * (x) (y)) 8) 4);

[hear] (((? x / ? y / = 5 / * (x) (y)) 1) 5);

[hear] (((? x / ? y / = 27 / * (x) (y)) 3) 9);

[hear] ((((? z /
? x /
? y /
= (z) /
* (x) (y))
60)
15)
4);

[hear] ((((? z / ? x / ? y / = (z) / * (x) (y)) 0)
5)
0);

[hear] ((((? z /
? x /
? y /
= (z) /
* (x) (y))
165)
15)
11);

[hear] ((((? z /
? x /
? y /
= (z) /
* (x) (y))
104)
13)
8);

[hear] ((((? z /
? x /
? y /
= (z) /
* (x) (y))
36)
6)
6);

[hear] ((((? z / ? x / ? y / = (z) / * (x) (y)) 2)
2)
1);

[hear] ((((? z /
? x /
? y /
= (z) /
* (x) (y))
165)
15)
11);

[hear] ((((? z /
? x /
? y /
= (z) /
* (x) (y))
70)
10)
7);